Toxicology studies of tetrabromobisphenol A in F344/NTac rats and B6C3F1/N mice and toxicology and carcinogenesis studies of tetrabromobisphenol A in Wistar Han [Crl:WI(Han)] rats and B6C3F1/N mice (gavage studies). (Natl Toxicol Program Tech Rep Ser, 2014)
Tetrabromobisphenol A is a flame retardant used in epoxy resin circuit boards, in electronic enclosures (of polycarbonate-acrylonitrile-butadiene-styrene plastics), in paper, and in textiles. It may also be used as a chemical intermediate for the synthesis of other flame retardants. Tetrabromobisphenol A was nominated by the NIEHS for toxicity and carcinogenicity studies based on its high production volume, the potential for widespread human exposures, and the absence of standard toxicity and carcinogenicity studies reported in the scientific literature. Male and female F344/NTac rats and B6C3F1/N mice were administered tetrabromobisphenol A (purity of greater than 99%) in corn oil by gavage for 3 months, and male and female Wistar Han [Crl:WI(Han)] rats (referred to as Wistar Han rats) and B6C3F1/N mice were administered tetrabromobisphenol A (purity of approximately 99%) in corn oil by gavage for 2 years. Genetic toxicology studies were conducted in Salmonella typhimurium, Escherichia coli, and mouse peripheral blood erythrocytes. (Abstract Abridged).